Survival in the forest : the Świrz Camp - Karten, Isidore 1914-1999 (Yad Vashem, 2013)
Dokumentarfilm zum Buch unter "youtube" u.d.T. Survival in the forest / Isidore Karten,s.a. : www.jewishpartisans.org